Discriminant evaluations on adolescent facial phenotypic morphological variations between two ethnic groups resident in Ibadan (Nigeria) metropolis – A regional baseline geometric pilot study - Abiodun Olowo; Michael Samuel; Moses Olusola Adetona (Forensic Science International: Reports, 2021)
Facial profiling for ethnic populations and representatives within Nigeria retains no documented evidence for distinguishing facial morphology and has at best remained ambiguous and incoherent. This investigation seeks to evaluate inter and intra tribal facial morphologic variations and sexual dimorphisms between two ethnic population groups co-resident within the same geographical area in Ibadan Oyo state. The study employed two-dimensional geometry and maximum parsimony tree using 10 facial landmarks on sampled two hundred and thirty-eight individuals comprising of one hundred and twenty three (123) females and one hundred and fifteen (115) males (17–25) years old taken from Ibadan. The result of this study revealed Yoruba and Igbo males had the highest Centroid size (3400 mm, 1500 mm) respectively. A Tukey pairwise comparison between Yoruba males and other three population groups was extremely significant (p<0.001). Static allometric variation along tribal genders revealed a 57.48% shape variation contribution relative to (≈ 43%) contributed by Centroid size emphasizing the significance of shape. Discriminant analysis for morphotype variability with pairwise comparison p values in each case (p<0.001 and 0.02) respectively in the genders investigated. Mahalanobis distance was similar in quantities of size and shape in both populations, distance between Yoruba and Igbo females was 2.77 but 2.05 between males. Igbo males vs Yoruba females was 1.96 and (2.03) for Yoruba genders. The result of this study will be invaluable in biological and cultural anthropologic studies, criminology, physiognomic and forensic researches.